If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+36=10-8x
We move all terms to the left:
5x+36-(10-8x)=0
We add all the numbers together, and all the variables
5x-(-8x+10)+36=0
We get rid of parentheses
5x+8x-10+36=0
We add all the numbers together, and all the variables
13x+26=0
We move all terms containing x to the left, all other terms to the right
13x=-26
x=-26/13
x=-2
| 45=4b=13 | | x-6/9+12=5x+7/2 | | 12x-10=4(x+2)+8x-17 | | a/4-7=a/4 | | 3a−1=81 | | 9(y-10)+15=9y-75 | | -2(3x-4)x6=-12-(3x-3) | | -2(3x-4)*6=-12-(3x-3) | | -4x-12=-9x+24 | | x2−121=0. | | 8*2+3y+4=0 | | x2+6x+8=0. | | (10*(-9)*(-14)*15)/((-5)*9*6)=x | | 5+6x-15=9x+8+3x | | 16-5(4y+8)-12=42 | | 4x=5(2x-7) | | 8x-4=7x-4 | | 7x-2=7-2x | | 5=5y+10 | | 11n-7=37 | | |5x+7|+13=26 | | (3+5x)+4=4 | | 5x-7=4×+3 | | 3(x+7=42 | | 18+(7x²-5)=1 | | 1x/2+9=14 | | 0=x^2-6x+4x-9 | | 2y²-50=0 | | 8x+4/3x=2 | | 20x/8=5 | | n/20+6=35 | | 2x2-12x+20=0 |